Anemia in HIV-positive patients treatedat A university hospital in Pernambuco – northeast of Brazil - Feitosa, Suelen Maria C; Cabral, Poliana C (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: anemia is the most frequent hematological complication in HIV-infected patients. Objective: to evaluate the frequency of anemia in patients with human immunodeficiency virus treated at Hospital das Clínicas de Pernambuco, during the period from March to October 2010. Methods: the study of case series consisting of 108 individuals of both sexes aged 19 to 59 years old in which the frequency of anemia and its association with some socioeconomic, demographic and clinical variables were rated. Results: a male predominance (60.2%) with an average age close to 40 years and precarious economic level (74.2% of patients with family income below two minimum wages) was observed. The frequency of anemia was high, 56.4% of the sample being mostly classified as normocytic (59.0% of anemic) and of moderate severity (49.2%). Anthropometric evaluation, 18.5% and 27.7% of patients were classified as underweight and overweight, respectively, and a high percentage of malnutrition was diagnosed by assessing the actions of the arm (Mid-arm Circumference (MC) = 64, 8%; Triceps Skinfold Thickness (TSF) = 72.3% and Mid-arm Muscle Circunference (MMC) = 49.1%). To examine the association between anemia and the variables studied were statistically significant associations with family income ≤ 2 minimum wages, with the level of CD4 < 200 cells/mm3 and with the occurrence of opportunistic infections. Conclusion: the high prevalence of anemia in this sample represents a warning given that this disorder has been linked to worsening of clinical status and increased risk of death in HIV-infected patients.